Poverty in Siak District, Riau Province: Its Issues and Contributing Factors - Wan Muhammad Yunus; Maryunani .; Khusnul Ashar; Ghozali Maskie (Institute of Research and Community Service, University of Brawijaya)
This research aims to determine and identify contributing factors to poverty in Siak District based on poverty level guidance. This research took place at Siak District by involving 273 respondents. They are classified into several groups; very poor, poor, near poor and susceptible poor. Multinomial logit is taken as an analysis tool for the research. It describes that poor probability to each level is different and more affected by conditional factors: (i) very poor: land availability and its ownership, weather, infrastructure, public accessibility, size of the family, dependency ratio, asset ownership and job status/level; (ii) poor: social capital and ethnical background; (iii) near poor: land ownership, weather, age, and level of education; (iv) susceptible poor: social isolation, size of the family, asset ownership and job level.